2000
DOI: 10.1002/(sici)1099-1077(200001)15:1<1::aid-hup153>3.0.co;2-1
|View full text |Cite
|
Sign up to set email alerts
|

A unifying hypothesis of Alzheimer's disease. III. Risk factors

Abstract: Normal ageing and Alzheimer's disease (AD) have many features in common and, in many respects, both conditions only differ by quantitative criteria. A variety of genetic, medical and environmental factors modulate the ageing-related processes leading the brain into the devastation of AD. In accordance with the concept that AD is a metabolic disease, these risk factors deteriorate the homeostasis of the Ca(2+)-energy-redox triangle and disrupt the cerebral reserve capacity under metabolic stress. The major gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
30
0
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 997 publications
0
30
0
1
Order By: Relevance
“…Identifying genetic factors may provide valuable information for targeting prevention and treatment strategies to individuals at increased risk for AD (30).…”
Section: Non-modifiable Risk Factorsmentioning
confidence: 99%
See 2 more Smart Citations
“…Identifying genetic factors may provide valuable information for targeting prevention and treatment strategies to individuals at increased risk for AD (30).…”
Section: Non-modifiable Risk Factorsmentioning
confidence: 99%
“…Head injuries may reduce brain reserve or induce alterations in neuronal metabolism or circuitry (30). One study suggests that head trauma is only a risk factor for individuals who carry the ApoE ε4 allele, although the mechanism for this interaction is unclear (52).…”
Section: Modifiable Risk Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…9 As with most complex diseases, LOAD is likely to be influenced not only by genetic, but also by environmental components. 10,11 Based on outcomes of studies in twins, Plassman et al 12 reported simple heritability estimates among various European populations at approximately 0.8, suggesting that environmental factors account for approximately 20% of variance in population susceptibility to AD.…”
mentioning
confidence: 99%
“…[15] Increased zinc intake can cause demyelinating diseases in human beings [16] and aluminium is responsible for development of dementia-type syndromes and postulated as one of the etiological agents of Alzheimer's disease. [17,18,19,20] Though iron is a bioessential element, its excess accumulation causes nephrotoxicity, induction of renal cell and heptacellular carcinoma have been well documented in the literature. [21,22,23,24] www.wjpps.com …”
Section: Introductionmentioning
confidence: 99%